Genome-wide screening of Oryza sativa ssp. japonica and indica reveals a complex family of proteins with ribosome-inactivating protein domains. (November 2017) - Wytynck, Pieter; Rougé, Pierre; Van Damme, Els J.M.
Abstract: Ribosome-inactivating proteins (RIPs) are cytotoxic enzymes capable of halting protein synthesis by irreversible modification of ribosomes. Although RIPs are widespread they are not ubiquitous in the plant kingdom. The physiological importance of RIPs is not fully elucidated, but evidence suggests a role in the protection of the plant against biotic and abiotic stresses. Searches in the rice genome revealed a large and highly complex family of proteins with a RIP domain. A comparative analysis retrieved 38 RIP sequences from the genome sequence of Oryza sativa subspecies japonica and 34 sequences from the subspecies indica. The RIP sequences are scattered over different chromosomes but are mostly found on the third chromosome. The phylogenetic tree revealed the pairwise clustering of RIPs from japonica and indica. Molecular modeling and sequence analysis yielded information on the catalytic site of the enzyme, and suggested that a large part of RIP domains probably possess N-glycosidase activity. Several RIPs are differentially expressed in plant tissues and in response to specific abiotic stresses. This study provides an overview of RIP motifs in rice and will help to understand their biological role(s) and evolutionary relationships. Graphical abstract: Highlights: The Oryza sativa genome contains a large and complex family of RIP sequences. RIP sequences in two rice subspecies are similar though not identical. Only part of the RIP sequences contains the conserved residues for the active site.